Pilot Project: analysis, development and projection - Tapia Abril, Verónica Emilia (Universidad de Cuenca, 2014)
Since the introduction of ICT in architecture and teaching, pedagogies of education have faced their learning paradigms change. Institutes of higher education have folded to this motion and have undergone a process of change by implementing multimedia elements in their subjects. Through the pilot project educational videos that aim to meet the highest standards of educational videos described by Van Dam have been developed. The project expects to generate educational videos for different departments of the Faculty of Architecture, which will be delivered promptly to teachers.Keywords: Pedagogy, video, architecture, Cuenca, Ecuador.